2015
DOI: 10.1007/jhep01(2015)019
|View full text |Cite
|
Sign up to set email alerts
|

A unified thermodynamic picture of Hořava-Lifshitz black hole in arbitrary space time

Abstract: Abstract:In this paper, we analyze the complete thermodynamic and phase transition phenomena of a black hole solution in Hořava-Lifshitz gravity in arbitrary space time. Nature of phase transition is studied using geometrothermodynamic and Ehrenfest's scheme of standard thermodynamics. We analytically check the Ehrenfest's equations near the critical point, which is the point of divergence in the heat capacity. Our analysis revels that this black hole exhibits a second order phase transition.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Theories nonlinear in curvature and/or fields also replicate similar behavior. These include black holes in higher [83,120,[198][199][200][201] and lower dimensions [176,202,203], Lovelock gravity [78,82,89,204,220], nonlinear electrodynamics [84,[87][88][89][90][91][92], Einstein-Yang-Mills gravity [205], black holes with scalar hair [57,202,[206][207][208][209], dyonic black holes [210], f(R) gravity [211], STU black holes [164], quasi-topological gravity [171], conformal gravity [212], Horava-Lifshitz black holes [189,213,214], Poincare gauge gravity [203], Lifshitz gravity [58,221], massive gravity [215][216][217][218][219], and others 28 . Most of these articles obtain the same qualitative phase behavior associated with swallowtai...…”
Section: Future Of Black Hole Chemistrymentioning
confidence: 99%
“…Theories nonlinear in curvature and/or fields also replicate similar behavior. These include black holes in higher [83,120,[198][199][200][201] and lower dimensions [176,202,203], Lovelock gravity [78,82,89,204,220], nonlinear electrodynamics [84,[87][88][89][90][91][92], Einstein-Yang-Mills gravity [205], black holes with scalar hair [57,202,[206][207][208][209], dyonic black holes [210], f(R) gravity [211], STU black holes [164], quasi-topological gravity [171], conformal gravity [212], Horava-Lifshitz black holes [189,213,214], Poincare gauge gravity [203], Lifshitz gravity [58,221], massive gravity [215][216][217][218][219], and others 28 . Most of these articles obtain the same qualitative phase behavior associated with swallowtai...…”
Section: Future Of Black Hole Chemistrymentioning
confidence: 99%
“…This work is the further elaboration of Dolan's work where the critical behaviour of the AdS black holes in the extended phase space was discussed and the analogy with the Van der Waals was found [12]. Based this interesting work, the thermodynamics of various complicate spacetimes were discussed and many significative critical phenomena were found [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 83%
“…For a singularity space-time, Banerjee et al found that the Reissner-Nordström-AdS/Kerr-AdS BH phase transition is the second-order and the main reason that leads to the second-order phase transition is the BH charge/angular momentum [20,21]. Extensive study in this framework for the singularity space-time in various gravity theoretical models shows that the phase transition grade would be different for various BHs, but the BHs' critical behavior is similar to the vdW system [22][23][24][25][26][27][28][29][30][31]. These results are based on the BHs' specific heat diverges at the critical point.…”
Section: Introductionmentioning
confidence: 98%